2015
DOI: 10.4236/ajibm.2015.55029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organizational Justice and Psychological Empowerment on Perceived Organizational Performance: The Mediating Role of Organizational Citizenship Behaviour

Abstract: The present research analysed the relationships among organizational justice, psychological empowerment, organizational citizenship behaviour, and perceived organizational performance. For this purpose, the data was collected from 260 employees working in different banks in Pakistan. Baron and Kenny's regression approach was used to test the mediation effect. In addition, Sobel test by Preacher, K. J. & Hayes, A. F. was also used for bootstrapping in the SPSS. All the alternate hypotheses of the study were acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
(33 reference statements)
1
9
0
2
Order By: Relevance
“…Shin et al (2015) explained that positive attitudes of employees resulting from procedurally fair workplaces and decisions increase their voluntary cooperation and performance to complete various organizational functions efficaciously which thereby, advances the bottom line performance of the firm. Another study by Azeem et al (2015) purported that there exist a positive association between organizational justice (procedural and distributive justice) and perceived organizational performance, though partially mediated by the organizational citizenship behaviour. Thus, the following hypothesis can be raised:…”
Section: Diversity-focused Huma Resources Practices Procedural Justice and Perceived Firm Performancementioning
confidence: 99%
“…Shin et al (2015) explained that positive attitudes of employees resulting from procedurally fair workplaces and decisions increase their voluntary cooperation and performance to complete various organizational functions efficaciously which thereby, advances the bottom line performance of the firm. Another study by Azeem et al (2015) purported that there exist a positive association between organizational justice (procedural and distributive justice) and perceived organizational performance, though partially mediated by the organizational citizenship behaviour. Thus, the following hypothesis can be raised:…”
Section: Diversity-focused Huma Resources Practices Procedural Justice and Perceived Firm Performancementioning
confidence: 99%
“…Mohammad et al (2016) revealed that justice showed direct effect on citizenship behaviour directed toward individual and organisation alike. Azeem et al (2015) revealed that organisational citizenship behaviour partially mediated the relationship between organisational justice and perceived organisational performance. The study also found that organisational citizenship behaviour fully mediated the relationship between psychological empowerment and perceived organisational performance.…”
Section: Relationship Between Organisational Justice and Citizenship mentioning
confidence: 97%
“…In short, a vision must be future situated. However, another idea of vision is to accumulate all components from current continuous situations and forerunners of business (Azeem et al, 2015). Afterwards, coordinate them for the suspicion and direction for the future activities and rules.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…Transformational management can plan the moving vision to interest the employees or staff in the vast organization, where the work drive is more extensive as a contrast with the small organizations and also to fulfill the workers (Sabharwal, 2014). The top managers with giving reasonable vision inspiration to key constituents of the organization by saying what cannot avoid being what is great either awful, now or how it would be upgraded in the nearby future (Azeem et al, 2015). To keep the company on immense improvement, directors need to interface with key constitutes particularly customers, staff, and accessories of the business and more especially the fulfilled staff through a spurring and attractive organizational vision (Bisharat et al, 2016).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation